Efektivitas Metode Token Ekonomi Dalam Mengurangi Class Distruption pada Siswa Attention Deficit Hyperactivity Disorder Kelas V di SD Negeri 16 Takengon - Putri Sabila; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2022)
This study discusses the effectiveness of the token economy method in reducing class disruption in class V attention deficit hyperactivity disorder (ADHD) students at SD Negeri 16 Takengon, the aim is to prove the effectiveness of token economy in reducing out-of-class behavior disorders in ADHD children. This research is a quantitative research with an experimental approach, in the form of single subject research (SSR). The study design used A-B-A, where , baseline (A1), intervention (B), baseline (A2). Data collection techniques in this study were direct observation and using instruments for ADHD children. Data collection is done by filling in the frequency during the learning process. Based on the results of the analysis of the student's condition showed up and down in the behavior. In the intervention process, students experienced a decrease in class disruptive behavior in the form of leaving the class when the Economic Token Method was given, indicating that the Economic Token Method was effective in reducing class disruptive behavior in the form of leaving the classroom during the teaching and learning process.